2019
DOI: 10.4097/kja.d.17.00081
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized controlled double-blind study comparing auscultation and lung ultrasonography in the assessment of double lumen tube position in elective thoracic surgeries involving one lung ventilation at a tertiary care cancer institute

Abstract: LUS, as compared to auscultation, is a superior method in assessment of lung isolation for determining position of DLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…Moreover, despite the usefulness of lung sonography, several previous studies have shown that the diagnostic efficacy of lung sonography in determining the LDLT position can be variable (accuracy of 70% or 84%–89%, sensitivity of 88% or 94%, and specificity of 75% or 56%). 6 , 7 , 15 These variable results of diagnostic efficacy with lung sonography may imply that despite providing useful and accurate information in lung isolation techniques, the findings of lung sonography may be affected by various factors such as the investigator’s skill, the device used, or the patient’s condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, despite the usefulness of lung sonography, several previous studies have shown that the diagnostic efficacy of lung sonography in determining the LDLT position can be variable (accuracy of 70% or 84%–89%, sensitivity of 88% or 94%, and specificity of 75% or 56%). 6 , 7 , 15 These variable results of diagnostic efficacy with lung sonography may imply that despite providing useful and accurate information in lung isolation techniques, the findings of lung sonography may be affected by various factors such as the investigator’s skill, the device used, or the patient’s condition.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Even in thoracic surgery, lung sonography can be a superior method for determining the DLT position. 7 However, this technique requires clinical experience, and its efficacy may thus differ between novice and expert investigators. We compared the diagnostic efficacy of lung sonography between novices and experts for verifying appropriate insertion of an LDLT.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50] LUS also can be used for confirmation of double-lumen tube placement during lung isolation maneuvers. 51,52 Lichtenstein et al incorporated LUS into their bedside lung ultrasound in emergency (BLUE) protocol for the diagnosis of acute respiratory failure, 39,53 and FALLS (fluid administration limited by LUS) protocol for the management of acute circulatory failure. 53,54 Table 5 highlights the diagnostic utility of LUS signs, along with focused cardiac ultrasound, to help differentiate various lung diseases.…”
Section: Lus Versus Other Imaging Modalitiesmentioning
confidence: 99%
“…Many of the studies evaluating lung ultrasound were performed in patients who were scheduled for elective surgery with limited intrinsic lung disease. [3][4][5][6] Pulmonary parenchymal with consolidation or atelectasis may impede lung ultrasound as lung sliding is observed only in ventilated areas. Therefore, even if two-lung ventilation is performed, Figure 3 Bar code sign in an adult.…”
Section: Limitations Of Lung Ultrasonographymentioning
confidence: 99%
“…2 Similar results have been reported when using a double lumen endotracheal tube for OLV. [3][4][5][6] To date, there are a limited number of case reports regarding the use of lung ultrasound in children and no prospective clinical trials. There is increasing clinical use of point-of-care ultrasound (POCUS) to identify effective lung separation thereby eliminating the need for bronchoscopy and limiting inaccuracies with auscultation.…”
Section: Introductionmentioning
confidence: 99%